Incremental Prognostic Use of Left Ventricular Global Longitudinal Strain in Asymptomatic/Minimally Symptomatic Patients With Severe Bioprosthetic Aortic Stenosis Undergoing Redo Aortic Valve Replacement. (June 2017) - Naji, Peyman; Shah, Shailee; Svensson, Lars G.; Gillinov, A. Marc; Johnston, Douglas R.; Rodriguez, L. Leonardo; Grimm, Richard A.; Griffin, Brian P.; Desai, Milind Y.
Abstract : Background—: With improved survival of patients undergoing primary bioprosthetic aortic valve replacement (AVR), reoperation to relieve severe prosthetic aortic stenosis (PAS) is increasing. Timing of redo surgery in asymptomatic/minimally symptomatic patients remains controversial. Left ventricular (LV) global longitudinal strain (GLS) is a marker of subclinical LV dysfunction. In asymptomatic/minimally symptomatic patients with severe PAS undergoing redo AVR, we sought to determine whether LV-GLS provides incremental prognostic use. Methods and Results—: We studied 191 patients with severe bioprosthetic PAS (63±16 years, 58% men) who underwent redo AVR between 2000 and 2012 (excluding mechanical PAS, severe other valve disease transcatheter AVR, and LV ejection fraction <50%). Society of Thoracic Surgeons score was calculated. Standard echocardiography data were obtained. LV-GLS was measured on 2-, 3-, and 4-chamber views using velocity vector imaging. Severe PAS was defined as aortic valve area <0.8 cm 2, mean aortic valve gradient ≥40 mm Hg, and dimensionless index <0.25. A composite outcome of death and congestive heart failure admission was recorded. At baseline, mean Society of Thoracic Surgeons score, LV ejection fraction, mean aortic valve gradients, and right ventricular systolic pressure were 7±6, 58±6%, 54±10 mm Hg and 40±14 mm Hg, whereas 50% had >2+ aortic regurgitation. Median LV-GLS was −14.2% (−11.4, −17.1%). At 4.2±3 years, 41 (22%) patients met the composite end point (2.5% deaths and 1% strokes at 30 days postoperatively). On multivariable Cox survival analysis, LV-GLS was independently associated with longer-term composite events (hazard ratio, 1.21; 95% confidence interval, 1.10–1.33), P <0.01. The C statistic for the clinical model (Society of Thoracic Surgeons score, degree of aortic regurgitation, and right ventricular systolic pressure) was 0.64 (95% confidence interval 0.54–0.79), P <0.001. Addition of LV-GLS to the clinical model increased the C statistic significantly to 0.71 (95% confidence interval 0.58–0.81), P <0.001. Conclusions—: In asymptomatic/minimally symptomatic patients with severe bioprosthetic PAS undergoing redo AVR, baseline LV-GLS provides incremental prognostic use over established predictors and could potentially aid in surgical timing and risk stratification.